Me & Patsy, kickin' up dust : my friendship with Patsy Cline - Lynn, Loretta; Russell, Patsy Lynn (Grand Central Publishing, 2020)
"Me & Patsy Kickin' Up Dust shares the 'important and inspiring' (Miranda Lambert) never-before-told complete story of the remarkable relationship between country music icons Patsy Cline and Loretta Lynn. Loretta Lynn and the late Patsy Cline are legends--country icons and sisters of the heart. For the first time ever Loretta tells their story: a celebration of their music and their relationship up until Patsy's tragic and untimely death. Full of laughter and tears, this eye-opening, heartwarming memoir paints a picture of two stubborn, spirited country gals who'd be damned if they'd let men or convention tell them how to be. Set in the heady streets of the 1960s South, this nostalgia ride shows how Nashville blossomed into the city of music it is today. Tender and fierce, Me & Patsy Kickin' Up Dust is an up-close-and-personal portrait of a friendship that defined a generation and changed country music indelibly--and a meditation on love, loss and legacy"--Amazon.com.